2019
DOI: 10.3390/s19204485
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Technology on People with Autism Spectrum Disorder: A Systematic Literature Review

Abstract: People with autism spectrum disorder (ASD) tend to enjoy themselves and be engaged when interacting with computers, as these interactions occur in a safe and trustworthy environment. In this paper, we present a systematic literature review on the state of the research on the use of technology to teach people with ASD. We reviewed 94 studies that show how the use of technology in educational contexts helps people with ASD develop several skills, how these approaches consider aspects of user experience, usabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(102 citation statements)
references
References 83 publications
1
94
0
7
Order By: Relevance
“…Finally, in order to manage the smart adaptation of the worker to the workplace environment, and for him or her to execute the work in an adapted way, there are KETs that provide inclusion and regulation of the worker within the workplace [ 96 ]. Cyber-physical systems have also been employed not only to promote better results for both employees and employers, but also for the improvement of behavior and creativity in the workspace.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in order to manage the smart adaptation of the worker to the workplace environment, and for him or her to execute the work in an adapted way, there are KETs that provide inclusion and regulation of the worker within the workplace [ 96 ]. Cyber-physical systems have also been employed not only to promote better results for both employees and employers, but also for the improvement of behavior and creativity in the workspace.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, such as those that evaluate people with autism spectrum disorder, allow us to understand the importance of being specific in the profile to provide concrete solutions to specific needs [ 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that early comprehensive and targeted behavioral interventions can improve social communication and reduce anxiety and aggressiveness. (7) Cognition of color is a part of early cognitive learning in children, but it is of great significance for future communication learning. However, many autistic children are different from ordinary children in color perception, and have differences in color preference and color discrimination ability.…”
Section: Related Referencesmentioning
confidence: 99%